Neural mechanisms underlying the conditioned pain modulation response: a narrative review of neuroimaging studies. Issue 1 (13th January 2023) - Nahman-Averbuch, Hadas; Timmers, Inge
Abstract: Processing spatially distributed nociceptive information is critical for survival. The conditioned pain modulation (CPM) response has become a common psychophysical test to examine pain modulation capabilities related to spatial filtering of nociceptive information. Neuroimaging studies have been conducted to elucidate the neural mechanisms underlying the CPM response in health and chronic pain states, yet their findings have not been critically reviewed and synthesized before. This narrative review presents a simplified overview of MRI methodology in relation to CPM assessments and summarizes the findings of neuroimaging studies on the CPM response. The summary includes functional MRI studies assessing CPM responses during scanning as well as functional and structural MRI studies correlating indices with CPM responses assessed outside of the scanner. The findings are discussed in relation to the suggested mechanisms for the CPM response. A better understanding of neural mechanisms underlying spatial processing of nociceptive information could advance both pain research and clinical use of the CPM response as a marker or a treatment target.